Health Outcomes After Disaster for Older Adults With Chronic Disease: A Systematic Review. (7th September 2019) - Bell, Sue Anne; Horowitz, Jennifer; Iwashyna, Theodore J
Abstract: Background and Objectives: This review synthesizes the current literature surrounding chronic disease outcomes after weather- and climate-related disasters among older adults. The associations between exposure of older adults to weather- and climate-related disasters and the primary outcomes of diabetes, end-stage renal disease (ESRD), congestive heart failure (CHF), and chronic obstructive pulmonary disease (COPD) were examined. Research Design and Methods: A systematic review of studies reporting on clinical outcomes of four chronic diseases after disaster exposure was performed. Under the direction of an informationist, the databases PubMed, Scopus, EMBASE, and Web of Science (Science and Social Science Citation Index) were searched from inception to July 2019. Results: Of 5, 229 citations identified, 17 articles met the study criteria. Included articles were retrospective observational in nature and focused on earthquakes (24%, n = 4), hurricane (41%, n = 7), and wildfire (35%, n = 6) disasters. Outcome data by disease process included COPD (35%, n = 6), ESRD (41%, n = 7), CHF (24%, n = 4), and diabetes (29%, n = 5). Three main categories were identified: access to health care, postdisaster health care utilization, and study rigor. The age-stratified analyses reported in this review found multiple instances where disasters have limited or insignificant effects on older adults relative to younger populations. Discussion and Implications: Disaster research faces unique methodological challenges, and there remains a need for data-driven conclusions on how best to care for older adults before, during, and after disasters. To encourage consistent dialogue among studies, we advocate for the use of rigorous and standardized scientific methodology to examine the health impacts of disasters on adults with chronic disease.